Fried food consumption and the risk of pancreatic cancer: A large prospective multicenter study - Zhong, Guo-Chao; Zhu, Qian; Gong, Jian-Ping; Cai, Dong; Hu, Jie-Jun; Dai, Xin; Gong, Jun-Hua (Frontiers in Nutrition, 2022)
Background and Aims: Whether fried food consumption is associated with the risk of pancreatic cancer remains elusive. We aimed to examine this association in a US population. Methods: A population-based cohort of 101729 US adults was identified. Fried food consumption was assessed with a validated food frequency questionnaire. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated. Explanatory analyses were conducted to identify main contributor(s) to the observed association. Results: During an average follow-up of 8.86 years (900871.2 person-years), 402 pancreatic cancer cases occurred. High consumption of total fried foods (deep-fried plus pan-fried foods; HRquartile 4 vs. 1 0.71, 95% CI 0.51 to 0.99, Ptrend=0.047) and deep-fried foods (HRquartile 4 vs. 1 0.64, 95% CI 0.47 to 0.88, Ptrend=0.011), but not pan-fried foods (HRquartile 4 vs. 1 0.98, 95% CI 0.73 to 1.32; Ptrend=0.815), was found to be associated with a reduced risk of pancreatic cancer in a nonlinear dose–response manner, which was not modified by predefined stratification factors and persisted in sensitivity analyses. In explanatory analyses, only chip consumption was found to be inversely associated with the risk of pancreatic cancer; consistently, the initial significant associations between total fried food and deep-fried food consumption and the risk of pancreatic cancer changed to be non-significant after omitting or further adjusting for chip consumption. Conclusions: Consumption of deep-fried foods, but not pan-fried foods, is inversely associated with the risk of pancreatic cancer in this US population. The role of deep-fried foods in reducing the risk of pancreatic cancer appears to be mainly attributable to chips. More studies are needed to confirm our findings in other populations and settings.